2018
DOI: 10.1097/icb.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Hypoplasia: Diagnosis Using Optical Coherence Tomography Angiography

Abstract: To the best of our knowledge this is the first report of findings in foveal hypoplasia examined by angio-optical coherence tomography. Optical coherence tomography angiography is an easy, rapid, and noninvasive tool that allows imaging of the retinal microvasculature without intravenous dye injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“… 7 The absent FAZ of both the SVC and DVC are also similar findings seen in other etiologies of foveal hypoplasia. 8 , 9 , 10 In a small sample of foveal hypoplasia subjects, Pakzad-Vaezi et al 9 observed that the FAZ's in the DVC of eyes with albinism were less developed than both normal eyes and eyes with idiopathic foveal hypoplasia. They also noted that the eyes with albinism tended to have worse visual acuity compared to eyes with idiopathic foveal hypoplasia and raised the question as to whether this was due in part to a less developed FAZ.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The absent FAZ of both the SVC and DVC are also similar findings seen in other etiologies of foveal hypoplasia. 8 , 9 , 10 In a small sample of foveal hypoplasia subjects, Pakzad-Vaezi et al 9 observed that the FAZ's in the DVC of eyes with albinism were less developed than both normal eyes and eyes with idiopathic foveal hypoplasia. They also noted that the eyes with albinism tended to have worse visual acuity compared to eyes with idiopathic foveal hypoplasia and raised the question as to whether this was due in part to a less developed FAZ.…”
Section: Discussionmentioning
confidence: 99%
“…OCT angiography is a simple, fast and non-invasive method for imaging the retinal blood vessels in the macular area. In foveal hypoplasia, it can reveal the lack of a foveal avascular zone in the superficial and deep capillary layers (Pakzad-Vaezi et al, 2017;Sánchez-Vicente et al, 2018). In our case, the patient had the absence of a foveal avascular zone in both eyes.…”
Section: Discussionmentioning
confidence: 50%
“…Our patient had no foveal pit, with persistence of all the inner retinal layers and outer plexiform layer, outer nuclear layer widening, and outer segment lengthening in the foveolar area, which makes it a grade 2 with a visual acuity of 20/32 according to Thomas et al [2]. FH and FH are commonly bilateral [46]. In our case, the differential diagnosis includes an epiretinal membrane, which may simulate the absence of the foveal pit [7].…”
Section: Discussionmentioning
confidence: 85%